Effect of emulsifying salts containing potassium on the melting properties of block‐type dairy cheese analogue. (19th March 2014) - Schatz, Kristina; Hoffmann, Wolfgang; Schrader, Katrin; Maurer, Andrea
<x xml:space="preserve">Abstract</x> Substituting sodium with potassium in emulsifying salts of pasteurized block‐type dairy cheese analogues was investigated. Rennet casein and butter were used as protein and fat sources for the manufacture of a product with 51% dry matter and 50% fat in dry matter. Different emulsifying salt blends contained sodium or potassium citrate and sodium polyphosphate. The cheese analogues were tested for their melting properties by oscillation rheometry and by empirical tests for meltability and fat release after 2 days, 4 and 12 weeks of cold storage. A recipe containing about 60% less sodium and a typical standard recipe without potassium showed very similar results during 4 weeks of cold storage.